2018
DOI: 10.1037/hea0000655
|View full text |Cite
|
Sign up to set email alerts
|

Family obligations and asthma in youth: The moderating role of socioeconomic status.

Abstract: Objective: Fulfilling family obligations— providing instrumental help to and spending time with family— is a common aspect of family relationships. However, whether fulfilling these obligations links with physical health remains unclear. This study investigated whether fulfilling family obligations was associated with asthma outcomes among youths, and whether these associations differed depending on family socioeconomic status (SES). Method: Participants were 172 youths aged 8 to 17 years (Mage = 12.1; 54% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…They also converge with prior research indicating that familism behaviors can be both costly and beneficial, depending on context. Specifically, past studies have shown that whereas familism behaviors covary with worse asthma outcomes in low-SES youth (Lam et al, 2018), they relate to lower inflammatory biomarkers and better psychological health when the behaviors are viewed favorably (Fuligni et al, 2009; Hooper et al, 2012). Our findings provide further evidence that the impact of familism behaviors varies depending on individual and contextual factors and extend prior work by linking familism to inflammatory processes at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also converge with prior research indicating that familism behaviors can be both costly and beneficial, depending on context. Specifically, past studies have shown that whereas familism behaviors covary with worse asthma outcomes in low-SES youth (Lam et al, 2018), they relate to lower inflammatory biomarkers and better psychological health when the behaviors are viewed favorably (Fuligni et al, 2009; Hooper et al, 2012). Our findings provide further evidence that the impact of familism behaviors varies depending on individual and contextual factors and extend prior work by linking familism to inflammatory processes at the cellular level.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study of older adolescents found that family assistance was associated with higher levels of inflammation; however, adolescents who derived greater meaning from helping their families had lower levels of inflammatory biomarkers than their peers who derived little or no meaning (Fuligni et al, 2009). A more recent study similarly found that providing tangible assistance to and spending time with the family more frequently were associated with worse asthma outcomes in youth, but only among those from disadvantaged backgrounds (Lam et al, 2018). In addition to socioeconomic context and meaning attached to familism-related behaviors, ethnicity may also be an important moderator.…”
Section: Familism Behaviors and Links To Healthmentioning
confidence: 99%
“…Average levels of family assistance are longitudinally associated with higher levels of inflammation (Fuligni et al, 2009), and inflammation is positively associated with physical pain (Parkitny et al, 2013). Similarly, cross-sectional research shows that greater family obligations are associated with greater airway inflammation and parent-reported asthma symptoms among adolescents in low SES homes (Lam et al, 2018). Moreover, adolescents who provide significant, time-consuming, ongoing amounts of family caregiving experience more physical health problems (Becker, 2007; Hibbert, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Family assistance has been positively associated with inflammation (Fuligni et al, 2009), and inflammation is positively associated with physical pain (Parkitny et al, 2013). Moreover, fulfilling family obligations is associated with greater airway inflammation and parent-reported asthma symptoms among adolescents in low socioeconomic status (SES) homes (Lam et al, 2018). Similarly, adolescents who provide significant, time-consuming, ongoing amounts of family work (e.g., caregiving for a family member) are more likely to experience physical health problems (Hibbert, 2010).…”
Section: Home As a Context For Physical Health And Developmentmentioning
confidence: 99%